Trichobezoar presenting as gastric outlet obstruction: a case report - Bhardwaj, Sushma; Mir, Zahid I.; Singh, Hardeep; Gupta, Gunjan; Singh, Hemath; Bhardwaj, Mahak (International Surgery Journal, 2022)
Bezoars are results from accumulation of swallowed solid foreign material in the gastrointestinal tract. Typically, trichobezoars are diagnosis is based on Clinical history, radiological evidences. Surgical or endoscopic intervention is the treatment documented. In this case we present a case report of a teenage female of 16 year old diagnosed and operated for trichobezoar.